2020
DOI: 10.1111/josh.12899
|View full text |Cite
|
Sign up to set email alerts
|

Concussion Experiences in New England Private Preparatory High School Students Who Played Sports or Recreational Activities

Abstract: BACKGROUND Sports‐ and recreation‐related (SRR) activities are a major cause of adolescent concussions. Most adolescent SRR concussion research has been conducted among public school students. As private schools are qualitatively different from public schools (eg, location, socioeconomic status, sports played), this study explores the concussion experiences of a large group of private high school students. METHODS We surveyed 2047 New England private preparatory high school students who played sports or engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Research by Jiminez et al 50 found Hispanic students received significantly less concussion education than non‐Hispanic White students prior to experiencing a TBI. Additional reports indicate middle, private, and urban schools also lack SRC education, policies, and procedures 51,52 . All of this evidence lends credence to Harvey's 49 suggestion that concussion education be retooled to take these differences into consideration.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Research by Jiminez et al 50 found Hispanic students received significantly less concussion education than non‐Hispanic White students prior to experiencing a TBI. Additional reports indicate middle, private, and urban schools also lack SRC education, policies, and procedures 51,52 . All of this evidence lends credence to Harvey's 49 suggestion that concussion education be retooled to take these differences into consideration.…”
Section: Discussionmentioning
confidence: 88%
“…Additional reports indicate middle, private, and urban schools also lack SRC education, policies, and procedures. 51,52 All of this evidence lends credence to Harvey's 49 suggestion that concussion education be retooled to take these differences into consideration. 31 Cournoyer and Tripp, 36 Register-Mihalik et al, 32 Hunt, 34 Kurowski et al, 35 Kurowski et al, 25 Myrdal et al 26…”
Section: Author Study Design Sample Characteristics Findingsmentioning
confidence: 82%
“…This can be accomplished by increasing awareness of the risks and dangers of concussion and guiding athletes to follow the rules when competing. Referees and sports officials can assist in enforcing safety standards of play when competing 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The 5th International Conference on Concussion in Sport defined SRC as a traumatic brain injury caused by biomechanical stresses to the head or body, which ultimately results in functional impairment and temporary neurologic deficits 33 . Concussions have been connected to a wide range of characteristics, such as prior head trauma, age, education, competitive level, attitude, gender, unexpected collision, neck stiffness, emotional risks, cervical strength, and cervical circumference 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation